Extracorporeal membrane oxygenation in critically ill patients with active hematologic and non-hematologic malignancy: a literature review - Filho, Roberto Rabello; Joelsons, Daniel; de Arruda Bravim, Bruno (Frontiers in Medicine, 2024)
Combined progress in oncology and critical care medicine has led to new aspirations and discussions in advanced life support modalities in the intensive care unit. Over the last decade, extracorporeal membrane oxygenation, previously considered unsuitable for oncologic patients, has become increasingly popular, with more diverse applications. Nevertheless, mortality remains high in critically ill cancer patients, and eligibility for extracorporeal membrane oxygenation can be extremely challenging. This scenario is even more difficult due to the uncertain prognosis regarding the underlying malignancy, the increased rate of infections related to intensive care unit admission, and the high risk of adverse events during extracorporeal membrane oxygenation support. With advances in technology and better management involving extracorporeal membrane oxygenation, new data on clinical outcomes can be found. Therefore, this review article evaluates the indicators for extracorporeal membrane oxygenation in different types of oncology patients and the possible subgroups that could benefit from it. Furthermore, we highlight the prognosis, the risk factors for complications during this support, and the importance of decision-making based on a multidisciplinary team in the extracorporeal membrane oxygenation indication.